Truly, we both loved Beauty dearly! : the story of Sleeping Beauty, as told by the good and bad fairies - Shaskan, Trisha Speed, 1973-; Tayal, Amit (North Mankato, MN : Picture Window Books, a Capstone imprint, 2014)
Introduces the concept of point of view through the good and bad fairies' retelling of the classic fairy tale "Sleeping Beauty"--
Keywords: Fairy tales; Humorous stories